2021
DOI: 10.3389/fpsyt.2021.655079
|View full text |Cite
|
Sign up to set email alerts
|

Lamotrigine Reduces Stress Symptoms of Chronic Anxiety in the Times of the Covid-19 Natural Catastrophe-A Case Report

Abstract: The SARS-CoV-2 pandemic has been a worldwide chronic, stress-inducing natural catastrophe associated with increased emotional challenging. Patients with Post-traumatic stress disorder (PTSD), self-injury behavior, and obesity are predisposed to aggravation of their symptoms at this time, requiring new therapeutic approaches to balance their disrupted neuro-hormonal stress axis. Here we present our observations of an off-label treatment with lamotrigine in an adolescent girl with PTSD, self-injury behavior, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(39 reference statements)
1
1
0
Order By: Relevance
“…Pham et al demonstrated that using the LTG made it possible to observe a reduction in stress-related symptoms, including self-injurious behavior, as well as a reduction in body weight, effects anticipated and supported by our prior fundamental research findings in people and animals. Additionally, a recurrence of the localized symptoms occurred after decreasing the treatment dose of LTG, which is consistent with earlier findings [ 90 , 91 ].…”
Section: Lamotrigine Potential For Repurposingsupporting
confidence: 92%
“…Pham et al demonstrated that using the LTG made it possible to observe a reduction in stress-related symptoms, including self-injurious behavior, as well as a reduction in body weight, effects anticipated and supported by our prior fundamental research findings in people and animals. Additionally, a recurrence of the localized symptoms occurred after decreasing the treatment dose of LTG, which is consistent with earlier findings [ 90 , 91 ].…”
Section: Lamotrigine Potential For Repurposingsupporting
confidence: 92%
“…A recent case study has reported that healthcare workers, veterans, and children may currently be particularly vulnerable to PTSD and stress- or fear-related disorders due to the COVID-19 pandemic [ 98 ]. In addition, there have been reports of successful cases of anxiety and stress relief by prescribing therapeutic drugs to such individuals [ 99 , 100 ]. However, the research on neurocircuitry approaches in the relationship between the COVID-19 pandemic and fear-related disorders remains inadequate.…”
Section: Discussionmentioning
confidence: 99%